Network governance in ASEAN: fostering regional cooperation and integration - Sundram, Pushpanathan (Frontiers in Political Science, 2025)
This article examines network governance (NG) within the context of the Association of Southeast Asian Nations (ASEAN) and its sectoral communities, specifically the ASEAN Economic Community, the ASEAN Political-Security Community, and the ASEAN Socio-Cultural Community. The goal is to explore NG’s importance in fostering cooperation among ASEAN member states and addressing regional challenges. The study begins by providing an overview of ASEAN and its objectives, highlighting the crucial role of NG in promoting collaboration and policymaking through ASEAN processes. It then offers a comprehensive literature review that evaluates the conceptual framework of NG and previous research related to its significance for ASEAN. The article further explores theories and scholarly works discussing NG within ASEAN, offering insights into key themes and discussions in the literature. Specific examples from the three sectoral communities are included based on an analysis of ASEAN NG mechanisms and structures. The evaluation of NG effectiveness in tackling regional challenges considers the contributions of state actors, such as government representatives and non-state actors (NSAs), including civil society organizations and private sector entities. This analysis reveals the inherent challenges and opportunities in implementing NG within ASEAN frameworks. It also underscores the importance of collaborative efforts between state actors and NSAs and the need for supportive institutional frameworks and mechanisms to enhance NG effectiveness in ASEAN. Overall, this article aims to deepen the understanding of NG within ASEAN, illuminating its role in promoting regional integration, addressing challenges, and advancing development across ASEAN’s three sectoral communities.